A plasmonic perfect absorber enhanced longwave infrared quantum dot infrared photodetector with high quantum efficiency. (27th February 2017) - Lu, Xuejun; Vaillancourt, Jarrod; Gu, Guiru
Abstract: In this paper, we report a quantum dot infrared photodetector (QDIP) embedded in a plasmonic perfect absorber (PPA) cavity designed at the plasmonic resonant wavelength of 8.2 µ m. The reflection spectra and the electric-field are simulated and found to have strong confinement at the resonant wavelength. The QDIP embedded in the PPA cavity was fabricated using our flip-chip bonding and fan-out reading based fabrication process. Strong photocurrent enhancement is observed at the resonant wavelength. Due to the PPA enhancement, a high quantum efficiency (QE) of 50% is achieved. The high QE QDIP demonstration indicates that the PPA enhancement is a promising approach to achieve high QE in QDIPs.